153k views
2 votes
Factor this polynomial completely
10 {x}^(2) - 11x + 3

User FloChanz
by
6.0k points

1 Answer

6 votes

Given:

There are given the equation:


10x^2-11x+3=0

Step-by-step explanation:

According to the question:

we need to find the factor of the given equation:

So,

From the equation:


\begin{gathered} 10x^(2)-11x+3=0 \\ 10x^2-6x-5x+3=0 \\ (2x-1)(5x-3)=0 \end{gathered}

Final answer:

Hence, the factor of the given equation is shown below:


(2x-1)(5x-3)=0

User Salmanulfarzy
by
6.1k points